2017
DOI: 10.1021/acs.energyfuels.6b03441
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economics of Biocarbon Production Processes under Norwegian Conditions

Abstract: This work deals with techno-economic analysis studies in the context of production of 8 various grade biocarbon for utilization as reducing agents in metallurgical industries. A 9 detailed process design was developed for wood handling, debarking, chipping, drying, 10 carbonization, and combined heat and power production using Aspen Plus for 10 ton per 11 day (TPD) biocarbon output. A Fortran based user defined function was developed for the 12 carbonization process by considering pressure, temperature and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Mochidzuki et al [30] reported that there is an internal structural change (strong cross-linking and aromatization of the structure) due to the higher carbonization degree (above 700 • C), which results in a reduction of the porosity and increasing electrical conductivity. These chars were carbon-rich materials which have the potential for use as carbon electrodes [31] or as reductant in metallurgical (e.g., silicon and ferrosilicon) industry [32].…”
Section: Feedstocks Characteristicsmentioning
confidence: 99%
“…Mochidzuki et al [30] reported that there is an internal structural change (strong cross-linking and aromatization of the structure) due to the higher carbonization degree (above 700 • C), which results in a reduction of the porosity and increasing electrical conductivity. These chars were carbon-rich materials which have the potential for use as carbon electrodes [31] or as reductant in metallurgical (e.g., silicon and ferrosilicon) industry [32].…”
Section: Feedstocks Characteristicsmentioning
confidence: 99%
“…The modelling framework and assumptions made regarding biocarbon production was to a large extent based on the work by Olszewski et al [42]. They present a techno economical evaluation of biocarbon production processes, with focus on Norwegian conditions and conclude that there are economic benefits by supplying logwood rather than wood chips to the end user of biocarbon.…”
Section: Biocarbon Productionmentioning
confidence: 99%
“…Replacement of fossil carbon (typically coal, char or coke) with more CO 2 -neutral biocarbon (charcoal and some woodchips) has been an important research area over the last decades [42,51]. Local production of biocarbon from virgin biomass offers several obvious integration opportunities in terms of energy recovery.…”
Section: Biocarbon Productionmentioning
confidence: 99%
“…One of the main applications of biochar is its use as a renewable fuel [71][72][73]. Carbonization products can be incinerated or co-incinerated in combined heat and power plants and power plants.…”
Section: Biochar In Environmental Conservationmentioning
confidence: 99%